SRG: Energy-Efficient Localized Routing to Bypass Void in Wireless Sensor Networks - Singh, Saurabh; Singh, Sarvpal; Prakash, Jay (ADCAIJ: Advances in Distributed Computing and Artificial Intelligence Journal, 2023)
The Shift Reverse Gradient (SRG) approach presents a void-size-independent hole bypassing scheme for wireless sensor networks. It does not require establishing any chain or hierarchical tree structure to ensure reliable delivery. The proposed Shift Reverse Gradient (SRG) offers an energy-efficient solution with minimal overhead and consumes minimum power. It has a communication overhead equivalent to greedy forwarding. We have shown through the simulation that SRG energy consumption is minimal and is not much affected by an increase in the void size like other existing void bypassing methods.